IMPROVING THE ORGANIZATIONAL AND ECONOMIC BASIS OF AGROCHEMICAL SERVICE IN UZBEKISTAN - Azamat Zaripbaevich Tabaev (International Journal on Economics, Finance and Sustainable Development, 2021)
The article presents the current state of development of the agrochemical services, the problems and factors affecting them, as well as scientific suggestions for the effective organization of the agrochemical services in agriculture